2014
DOI: 10.1016/j.bbadis.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic systemic P2X7 receptor blockade prevents experimental colitis

Abstract: Prophylactic systemic P2X7-R blockade is effective in the prevention of experimental colitis, probably due to a systemic anti-inflammatory action, interfering with a stress-inflammation amplification loop mediated by P2X7-R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 83 publications
8
75
0
14
Order By: Relevance
“…Using a mouse model of acute AOM/DSS-induced colonic inflammation, we found that P2rx7 À/À mice displayed reduced signs of inflammation. This finding is in agreement with recent studies demonstrating that prophylactic systemic blockade of the P2RX7 activity prevented TNBS-induced colitis in rats (12) and that overexpression of P2RX7 in the intestinal mucosa was associated with the pathogenesis of CD (34). In the current study, we found that P2RX7 inactivation using selective antagonists as well as genetic deletion of the P2rx7 gene attenuated the weight loss and the overall disease activity score (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using a mouse model of acute AOM/DSS-induced colonic inflammation, we found that P2rx7 À/À mice displayed reduced signs of inflammation. This finding is in agreement with recent studies demonstrating that prophylactic systemic blockade of the P2RX7 activity prevented TNBS-induced colitis in rats (12) and that overexpression of P2RX7 in the intestinal mucosa was associated with the pathogenesis of CD (34). In the current study, we found that P2RX7 inactivation using selective antagonists as well as genetic deletion of the P2rx7 gene attenuated the weight loss and the overall disease activity score (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported that P2RX7 is differentially expressed in the mucosa of patients with active and quiescent inflammatory bowel disease (IBD) and that its activation could be triggered in response to neutrophil transepithelial migration (8). These results, together with published data based on the use of P2RX7 antagonists or P2rx7 À/À mice, support the notion that P2RX7 participates in the initiation as well as in the regulation of the inflammatory response notably via the processing and release of IL1B (10)(11)(12). It is widely accepted that chronic inflammation can promote tumor development (13).…”
Section: Introductionsupporting
confidence: 57%
“…16) In addition, Marques et al reported that i.p. administration of P2X7R antagonists exhibited partial, but significant, prophylactic effects on experimental colitis in rats, 17) and almost the same finding was obtained in mice by Wan et al 18) Interestingly, in the study of Kurashima et al, it was clearly indicated that ATP-P2X7R-mediated activation of colonic mast cells followed by their accumulation in the colons is the initiation phase of colitis development by induction of not only inflammatory cytokines, but also chemokines and leukotrienes for infiltration of neutrophils into the colon, leading to subsequent exacerbation of intestinal inflammation. 16) Based on this, it is reasonable to consider that prophylactic oral per os (p.o.)…”
mentioning
confidence: 91%
“…14,15) In fact, systemic blockade of P2X7R is reported to be effective for prevention of experimental colitis. [16][17][18] Kurashima et al demonstrated that intraperitoneal (i.p. )…”
mentioning
confidence: 99%
“…Indeed, high levels of P2X7 receptor expression was observed in the intestinal mucosa of Crohn's disease patients 36) , and treatment with P2X7 inhibitors (e.g., A-740003, Brilliant Blue G, and KN-62) ameliorated experimental colitis 37) . These findings collectively implicate that extracellular ATP-P2X7 pathway is a novel therapeutic target in the treatment of intestinal receptors in different tissues 27) , P2X7 receptor expression was predominantly observed on mast cells in the colon 36) .…”
Section: Mast Cells Mediate the Development Of Intestinal Inflammatiomentioning
confidence: 99%